Natural Disaster and Vulnerability to Trafficking of Women and Girls in India - Dutta, Mondira (European Scientific Journal, ESJ, 2017)
Disasters seldom restrain to administrative and political boundaries and derecognizes international borders. These borders become the most vulnerable areas where laws are practically inapplicable uniformly across the international borders. Women moving out in search of livelihood options become easy prey to trafficking for commercial sexual exploitation and are also devoid of any knowledge on safe migration policies. India, Bangladesh and Nepal in South Asia have been identified as the major sources from where men, women and children get trafficked for the purposes of involuntary domestic servitude, bondage of debt, camel jockey, commercial sexual exploitation and so on. Human trafficking among the women and girls has been one of the largest in terms of magnitude and poses the greatest challenge more so when a disaster strikes! The present paper attempts to identify the vulnerability factors within the perspective of a natural disaster particularly for women and girls who fall prey to being trafficked from their home. The study is based on secondary sources of information that identify regions which are frequently hit by disaster and compares them to those regions which have a high potential for being trafficked. The study relies and relates with selected micro level field visits in some of these areas which are of high vulnerability. It highlights certain factors that have contributed significantly during a disaster such as the age specific sex ratio and cultural components within the hazard prone districts.